THE MEASUREMENT OF WIND SPEED AND DIRECTION BY SODAR - BRODNIANSKA, Zuzana (Trends in education, 2010)
In the present contribution measurement method of wind speed and direction and thermal structure at the atmosphere by Sodar is described. The movement of pollutants in the atmosphere is affected by air movements and therefore is of great importance in measuring wind speed and direction. This contribution will provide brief and clear description of operating principle that device. Student can use this description in the Technical Means of Measuring and Monitoring subject.
Keywords: Sodar; pollutants; atmosphere; wind speed and direction.